Protection Priority in Mountain Environment Using Analytic Hierarchy Process (AHP) on Kinabalu Park, Sabah - Latip, Normah Abdul; Ahmad, A. Ghafar; Marzuki, Azizan; Rais, Nadiatul Sarah Muhammad (Universiti Sains Malaysia, 2016)
Environmental degradation is one of the largest threats that are happening especially in protected areas. This is due to protected areas provide not only environmental benefits but also social and economic benefits to people and communities worldwide. Kinabalu Park, Sabah is declared by UNESCO as Malaysia’s first World Heritage Site in 2000 and the park is classified into category II (National Park). A national park is very closely related to naturebased tourism, being a symbol of a high-quality natural environment with a well-designed tourist infrastructure. Among the main reasons for people coming to Kinabalu Park is to enjoy the beauty of nature as its flora and fauna diversity and also the magnificent mountainous landscape. This paper focuses on prioritizing the environment aspect that being affected by the tourism activities and some of the acts of irresponsible visitors. If the environmental degradation continues, this might harm the environment on the long term basis. The method that will be using is Analytic Hierarchy Process (AHP) to prioritize the protection of the environment on the study area. It can help decision makers to prioritize on which matter that they need to focus more on and also enables to put more expert knowledge together allowing more precise decisions and moderating personal judgments.